ANALISIS PENGISIAN KEKOSONGAN JABATAN WAKIL BUPATI KABUPATEN LUWU TIMUR 2021-2026 - Haedar Djidar; Dandi Darmadi; Andi Besse Panangareng (Halu Oleo University, 2024)
Filling a vacant position is one of the important elements in Constitutional Law. Without being filled with officials (Ambtsdrager), the functions of state offices cannot run properly as they should. The problems in this study are: How is the regulation for filling the vacant position of Deputy Regent of East Luwu Regency, What are the obstacles in the process of filling the vacant position of Deputy Regent of East Luwu Regency, This study aims to analyze and how is the regulation for filling the vacant position of Deputy Regent of East Luwu Regency, To find out and examine the obstacles in the process of filling the vacant position of Deputy Regent of East Luwu Regency, This study was conducted using an empirical normative approach method, namely in the literature on political science, government science, and law, the terms power, authority, and authority are often found, this study was conducted in East Luwu Regency. The regulation for filling the vacant position of Deputy Regent of East Luwu Regency is still not perfect, because the DPR has rules of procedure related to the issue of electing a deputy regent, but it is not perfect so a special committee must improve the rules of procedure for electing the Deputy Regent of East Luwu Regency. The obstacle in the process of filling the vacant position of Deputy Regent of East Luwu Regency is due to a large number of supporting parties so it is difficult to obtain results through joint deliberations.